Peat Soil Stabilization using Lime and Cement - Mohd Zambri Nadhirah; Md. Ghazaly Zuhayr (E3S Web of Conferences, 2018)
This paper presents a study of the comparison between two additive Lime and Cement for treating peat soil in term of stabilization. Peat and organic soils are commonly known for their high compressibility, extremely soft, and low strength. The aim of this paper is to determine the drained shear strength of treated peat soil from Perlis for comparison purposes. Direct Shear Box Test was conducted to obtain the shear strength for all the disturbed peat soil samples. The quick lime and cement was mixed with peat soil in proportions of 10% and 20% of the dry weight peat soil. The experiment results showed that the addition of additives had improved the strength characteristics of peat soil by 14% increment in shear strength. In addition, the mixture of lime with peat soil yield higher result in shear strength compared to cement by 14.07% and 13.5% respectively. These findings indicate that the lime and cement is a good stabilizer for peat soil, which often experienced high amount of moisture content.